FEATURES OF IMPLEMENTATION TAX CONTROL IN UKRAINE AND FOREIGN COUNTRIES AND THEIR LEGAL REGULATION - Galushchak , I.Ye. (The actual problems of regional economy development, 2020)
The article deals with the peculiarities of implementation and general characteristics of tax control in foreign countries. The problems that arise in the field of tax control in Ukraine in comparison with foreign experience are noted. The main directions of perfection in the implementation of tax control are outlined. The types of tax inspections in foreign countries are given. The interaction between tax authorities of different states in the implementation of tax control is given. The stages of development of the practice of tax control in foreign countries are revealed. The most widespread practice of foreign countries have been forms of tax control, which provide for appropriate control measures by the tax authorities of the state, before which the taxpayer has a duty to pay taxes.